CHARACTERISTICS OF BODY POSTURE IN THE SAGITTAL PLANE AND FITNESS OF FIRST-FORM PUPILS FROM RURAL AREAS - Hanna Żukowska; Mirosława Szark-Eckardt; Radosław Muszkieta; T.S. Iermakova (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to find correlations between characteristics of body posture in the sagittal plane and fitness and endurance of first-form children from rural areas. Material: an analysis of more than 30 sources of scientific and educational literature. Results: the study involved 209 children, including 102 girls and 107 boys. They were children who lived in the country since they were born. To assess particular characteristics of body posture, the children were studied by means of the measuring equipment using the projection Moiré system. Motor skills were estimated using selected EUROFIT physical fitness tests (sitting forward bend, standing broad jump, handgrip, sit-and-reach, bent arm hang and 10 x 5 m shuttle run). The level of physical endurance was evaluated with the Harvard Step Test modified by Montoye. Conclusions: the conducted research reveals statistically significant correlations between the characteristics of body posture in the sagittal plane and selected EUROFIT physical fitness tests and physical endurance of the children involved in the study.